Optimizing the Use of Indonesian in Learning in the Digital Era - Anita Chandra Dewi; Wiliantika; Nurul Ainun; Muh Arsyil Putra; A. Yeyen Nur Anggraeni; Muh Fahiratul Akbar; Serni Tangke Padang (International Journal of Sustainability in Research, 2023)
There needs to be special efforts to increase the use of Indonesian in digital learning. This includes content development, delivery techniques, and utilizing the latest technology that supports the language. Using the literature study method, in this research the author obtained data from books, scientific works, documents and other relevant sources. This research shows how important it is to use Indonesian as best as possible when studying in the digital era. Even though English is considered an international language, especially in the digital world, Indonesian is still a good tool for communicating in learning in Indonesia. Limited Indonesian language resources are one of the main obstacles in this optimization process. The development of Indonesian language educational resources can be a strategic step for parties interested in the world of education in Indonesia. So far, positive student responses show that digital learning can still optimize Indonesian. Therefore, educators, platform developers and policy makers must work together to ensure that Indonesian gets its rightful place in the digital era.